Islamic Laws Of Hazrat Umar And Today’s Europe: A Research And Analytical Study - Muhammad Farhan Ur Rehman , Hafiz Muhammad Kashif , Prof. Dr Matloob Ahmad (Corresponding Author) , Muhammad Ajmal , Muhammad Bilal (Migration Letters, 2024)
This research and analytical study explores the Islamic legal framework established during the era of Hazrat Umar, the second caliph of Islam, and its relevance to contemporary Europe. By examining key aspects of Islamic jurisprudence during Hazrat Umar’s Caliphate, such as marriage and family law, criminal justice, economic transactions, and gov[1]ernance, this paper aims to compare and contrast these legal principles with modern European legal systems. Through case studies and examples, the analysis delves into the societal impact and perception of Islamic laws in Europe, addressing challenges and controversies surrounding their implementation. Furthermore, the study investigates strategies for legal reform and adaptation, highlighting opportunities for integrating Islamic legal principles within European legal frameworks. Ultimately, this research contributes to the understanding of the historical legacy of Hazrat Umar’s legal system and its potential implications for legal theory and practice in contemporary multicultural societies.